Jøderne, der blev akademikere - Panduro Juhl, Magnus (Rambam. Tidsskrift for jødisk kultur og forskning, 2016)
In 1798, the Danish King Christian VII decreed that the Danish-Jewish citizens could enter Latin schools, which gave further access to the University of Copenhagen. This article investigates to what extent the Jews utilised this opportunity to create academic careers. Danish-Jewish students from four randomised years in the 19th century (1812, 1837, 1866, and 1889) are examined, and quantitative data from student biographies and the Danish-Jewish Genealogical Database are used. The results show that Danish-Jewish students were overrepresented at Danish Latin schools compared to the Jewry population in general. Furthermore, a majority of the Danish-Jewish students earned degrees at the university and became part of the elite in Denmark. The careers of the students are compared to their fathers’ and it is shown that many of the students broke free from their social inheritance. Moreover, converts among the Danish-Jewish students are identified, and explanations for the conversions are discussed. Finally, migration patterns of the students are considered, and the common assumption about Jews moving from the province to Copenhagen in the 1800s is confirmed.